The Host Galaxy of OJ 287 Revealed by Optical and Near-infrared Imaging - Nilsson K; Kotilainen J; Valtonen M; Gomez JL; Castro-Tirado AJ; Drozdz M; Gopakumar A; Jeong S; Kidger M; Komossa S; Mathur S; Park IH; et al. (IOP PUBLISHING LTD, 2022)
The BL Lacertae object OJ 287 (z = 0.306) has unique double-peaked optical outbursts every similar to 12 yr, and it presents one of the best cases for a small-separation binary supermassive black hole (SMBH) system, with an extremely massive primary log (M-BH/M-circle dot). However, the host galaxy is unresolved or only marginally detected in all optical studies so far, indicating a large deviation from the bulge mass-SMBH mass relation. We have obtained deep, high spatial resolution i-band and K-band images of OJ 287 when the target was in a low state, which enable us to detect the host galaxy. We find the broadband photometry of the host to be consistent with an early-type galaxy with M-R = -22.5 and M-K = -25.2, placing it in the middle of the host galaxy luminosity distribution of BL Lacertae objects. The central supermassive black hole is clearly overmassive for a host galaxy of that luminosity, but not unprecedented, given some recent findings of other "overmassive" black holes in nearby galaxies.